Vomiting as the initial clinical presentation of myocardial infarction in children with anomalous left coronary artery from the pulmonary trunk - Bjelakovic, Bojko; Pejcic, Ljiljana; Parezanovic, Vojislav (The Turkish Journal of Pediatrics, 2008)
Anomalous origin of the left coronary artery from the pulmonary trunk is a rare condition. The clinical presentation is usually nonspecific and varies from completely asymptomatic form to sudden cardiac death. We report a two-month-old infant with vomiting as a presenting symptom of anomalous origin of the left coronary artery from the pulmonary trunk.